2012
DOI: 10.4995/wrs.2012.1032
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of dermatophytosis in meat rabbits with alopecia in Portugal

Abstract: An epidemiological dermatophytosis survey was carried out in farmed rabbits with alopecia in Northern and Central Portugal. Between August and October 2008, samples from suspected clinical cases of alopecia in meat rabbits on industrial farms were collected and cultured by conventional methods. Effects on the prevalence of several variables, such as breed, age, month of sample collection, configuration of the lesions and presence of concomitant infections in the rabbitries were evaluated using a logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Taiwan belongs to the sub-tropical and tropical regions; therefore, the hot and humid climate makes a suitable environmental condition for dermatophyte infection and transmission, and less seasonal variation on the prevalence of dermatophyte infection. In the present study, no gender-related differences in the prevalence were found, which is similar to the previous studies [ 7 , 12 , 17 , 20 , 45 , 53 ]. Although the findings of this study showed that the age ranges were not associated with dermatophyte infection in rabbits, age has been identified as a predisposing factor for dermatophytosis in rabbits, and young rabbits or immuno-compromised rabbits are considered to be the most susceptible to infection [ 11 , 17 , 45 , 50 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Taiwan belongs to the sub-tropical and tropical regions; therefore, the hot and humid climate makes a suitable environmental condition for dermatophyte infection and transmission, and less seasonal variation on the prevalence of dermatophyte infection. In the present study, no gender-related differences in the prevalence were found, which is similar to the previous studies [ 7 , 12 , 17 , 20 , 45 , 53 ]. Although the findings of this study showed that the age ranges were not associated with dermatophyte infection in rabbits, age has been identified as a predisposing factor for dermatophytosis in rabbits, and young rabbits or immuno-compromised rabbits are considered to be the most susceptible to infection [ 11 , 17 , 45 , 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, no gender-related differences in the prevalence were found, which is similar to the previous studies [ 7 , 12 , 17 , 20 , 45 , 53 ]. Although the findings of this study showed that the age ranges were not associated with dermatophyte infection in rabbits, age has been identified as a predisposing factor for dermatophytosis in rabbits, and young rabbits or immuno-compromised rabbits are considered to be the most susceptible to infection [ 11 , 17 , 45 , 50 ]. One possible reason is that the immune system has not completely developed, and there are lower levels of fungistatic fatty acids in the sebum of young rabbits [ 54 , 55 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with the findings of Moreira et al . [32] and that of Bhatia and Sharma [16] who found higher rates by direct examination than by culture when they studied skin samples obtained from dermatophytosis affected rabbits and humans, respectively, and concluded that direct examination was a rapid and efficient method for presumptive diagnosis of ringworm infection. However, it is at variance with the findings of Gupta et al .…”
Section: Discussionmentioning
confidence: 99%